PENDEKATAN HYBRID TSR-NN UNTUK PERAMALAN INFLOW OUTFLOW UANG KARTAL REGIONAL JAWA TIMUR - Indrasetianingsih, Artanti; Hermanto, Elvira Mustikawati Putri; Ilham, Mohamad; Rahmawati, Novi; Hariyanto, Intan Amelia (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2025)
The availability of currency circulating in society can influence the economic conditions of a country. The need for money increases when religious holidays approach, such as Eid al-Fitr and Christmas, as well as school holidays and the end of the year. Therefore, it is necessary to plan the need for currency, one of which is by forecasting the circulation of currency, both inflow and outflow. Forecasting is done to predict a value in the future based on historical data. This research aim was to predict the inflow and outflow of regional currency in East Java using the hybrid Time Series Regression (TSR) – Neural Network (NN) method. The methods in time series analysis used to predict are increasingly developing, as are hybrid methods, namely methods that combine several models to produce more accurate forecasts. The analysis results obtained show that the prediction of incoming and outgoing cash flows is better using the hybrid TSR-NN method because it produces a smaller RMSE value, namely 1,656.62, with a MAPE of 0.28 compared to the TSR method. The results of this study are expected to contribute to a hybrid approach for forecasting the regional currency inflow and outflow of East Java.